Perilaku Positif Mahasiswa Melalui Konten Kejujuran Dikalangan Teman Sebaya di UIN Fatmawati Sukarno Bengkulu - Nafizah Putri (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to examine the meaning of honesty in peer relationships and its impact on interpersonal dynamics. Using a qualitative approach, the research employed in-depth interviews with three informants aged 22–24 years. The findings indicate that honesty is understood as a core moral value that forms the foundation of trust, personal integrity, and a positive social environment. Honesty plays a crucial role in maintaining relationship stability and preventing interpersonal conflict. When dishonesty occurs, individuals’ responses depend on the severity and consequences of the behavior; repeated or harmful dishonesty tends to diminish trust and influence decisions regarding whether to maintain or distance oneself from the relationship. The study also reveals that open communication, consistency between words and actions, and the ability to keep promises serve as primary ways individuals implement and model honesty in daily interactions. Overall, the findings highlight that honesty is an essential element in building and sustaining the quality of peer relationships